TanDEM-X PolarDEM 90m for Antarctica and its Potential Use for Polar Hydrology - Wessel, Birgit; Osterkamp, Nicole; Huber, Martin; Roth, Achim (2020)
In this study we present the digital elevation model (DEM) for Antarctica produced by the TanDEM-X (TerraSAR add-on for digital elevation measurement) mission. The TanDEM-X Polar DEM 90 is a reduced version of the global TanDEM-X DEM with special adaptations. Holes were filled with additional acquisitions and water areas were flattened to avoid noisy height values. The resulting DEM from SAR interferometry is outstanding due to its resolution, accuracy, consistency and coverage completeness. The TanDEM-X Polar DEM-90 is freely available for scientific use and provides a high resolution dataset as basis for research, e.g. on climate change, in Antarctica. This study focuses on the application of this DEM for hydrology on the basis of several hydrological DEM based features: flow direction, flow accumulation, slope, streams and catchment boundaries. These features were developed for liquid water flow. Their application and usefulness for icy regions will be investigated in this study. The joint interpretation of hydrologic features with geophysical measurements, e.g. ice velocity and further hydrological elements like supra- and subglacial lakes may enable a more in detail understanding of the ongoing processes on the ice.